(untitled) (Boletin Médico de Postgrado, 2020)
Valvular heart disease represents a public health problem worldwide. The goal of this study was to determine the etiology of valvular disease in patients that attend the cardiac valvular pathology consult of the Centro Cardiovascular Regional ASCARDIO-Barquisimeto during the period 2002 to 2015. We reviewed 1760 medical charts and the results show that mitral regurgitation was the most frequent lesion (66.13%). In regards to aortic valvular pathology, severe aortic stenosis predominated in 69.2% of cases followed by mild aortic regurgitation (37.7%). The main cause was degenerative for both aortic stenosis and regurgitation (76.4% and 59.5%, respectively). With respect to mitral valve lesion, stenosis and severe regurgitation was more common (58.3%, and 42.4%, respectively), while the etiology of mitral stenosis and insufficiency was in most cases rheumatic. Tricuspid as well as pulmonary regurgitation was considered mainly functional. Pulmonary stenosis was exclusively congenital. This study provided information to evaluate the current situation of cardiac valvular disease in Lara state.